Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Factorisation using identities

Factorisation using identities

Example 4

Example 5 Important

Example 6

Example 8

Example 7 Important

Ex 12.2, 1 (i)

Ex 12.2, 1 (ii)

Ex 12.2, 1 (iii) Important

Ex 12.2, 1 (v)

Ex 12.2, 1 (viii)

Ex 12.2, 1 (vi)

Ex 12.2, 1 (iv) Important

Ex 12.2, 1 (vii) Important

Ex 12.2, 2 (i)

Ex 12.2, 2 (iii)

Ex 12.2, 2 (vi)

Ex 12.2, 2 (ii) Important

Ex 12.2, 2 (iv) Important

Ex 12.2, 2 (v) You are here

Ex 12.2, 2 (vii) Important

Ex 12.2, 2 (viii) Important

Ex 12.2, 4 (i)

Ex 12.2, 4 (ii) Important

Ex 12.2, 4 (iii)

Ex 12.2, 4 (iv) Important

Ex 12.2, 4 (v) Important

Last updated at May 29, 2023 by Teachoo

Ex 12.2, 2 Factorise. (v) 〖"(l + m)" 〗^2– 〖"(l – m)" 〗^2 〖"(l + m)" 〗^2– 〖"(l – m)" 〗^2 Using 𝑎^2− 𝑏^2 = (a + b) (a − b) Here a = (l + m) and b = (l − m) = [("l" + m) + ("l" − m)] [("l" + m) − ("l "− m)] = ["l" + m + "l" − m] ["l" + m − "l" + m] = (2"l") (2m) = 2 × 2 × "l" × m = 4"l"m